Viruses and human cancer - Hudnall, S. David (Springer New York, 2014)
Viruses and Human Cancer provides a comprehensive review of the seven currently known human tumor viruses and their associated cancers with an emphasis on epidemiology, clinicopathologic features, and pathogenesis. Chapters are written by internationally recognized experts, and all are generously illustrated with tables, diagrams, and photographic images. Viruses and Human Cancer serves as a concise review of the field of human tumor virology for virologists, pathologists, oncologists and infectious disease specialists. It is of great value to practicing physicians, residents and clinical fellows in these specialties.